The Effect of Liquid Organic Fertilizer Derived from Mustard Green Vegetable Waste on the Growth of Cayenne Pepper Plants (Capsicum frutescens) - Firna Amanda; Manap Trianto; Lestari M.P Alibasyah; Aan Febriawan; Amalia Buntu; Ika Istadewi; Lilies Tangge (Biology, Medicine, & Natural Product Chemistry, 2026)
Organic fertilizer is a type of fertilizer produced from natural materials derived from living organisms. One form of organic fertilizer is liquid organic fertilizer, which has the advantage of providing nutrients that are more readily available and easily absorbed by plants. This study aimed to analyze the effect of different concentrations of liquid organic fertilizer derived from mustard green vegetable waste on the growth of cayenne pepper plants (Capsicum frutescens L.). The study employed a Completely Randomized Design (CRD) consisting of five treatment levels: P0 (control), P1 5% (10 mL), P2 10% (20 mL), P3 15% (30 mL), and P4 20% (40 mL). Each treatment was replicated three times, resulting in a total of 15 experimental units. The observed parameters included plant height, stem diameter, and number of leaves. Data were analyzed statistically using Analysis of Variance (ANOVA), followed by the Least Significant Difference (LSD) test when significant differences were detected. The results showed that the application of liquid organic fertilizer derived from mustard green vegetable waste had a significant effect on plant height, stem diameter, and leaf number of cayenne pepper plants. Treatment P2 with a concentration of 10% (20 mL) produced the best results across all observed parameters. This finding indicates that this concentration was able to provide sufficient and balanced nutrients to support vegetative plant growth, whereas increasing the concentration to 15% and 20% did not result in a significant improvement in growth. Therefore, liquid organic fertilizer derived from mustard green vegetable waste has the potential to be utilized as an alternative organic fertilizer for enhancing the growth of cayenne pepper plants, with an optimum concentration of 10% (20 mL).